ACTIVITY OF JAVA ACID LEAF EXTRACT (Tamarandus indica L.) ON BLOOD GLUCOSE LEVELS OF RABBIT DRAIN INDUCED BY STREPTOZOTOCIN - Bunga Rimta Barus; Sofia Rahmi (JBIO: jurnal biosains (the journal of biosciences), 2022)
One of the plants commonly used as medicinal ingredients is tamarind leaf (Tamarindus indica L.). This plant belongs to the Leguminoceae family which has antidiabetic activity. This study aims to determine the antidiabetic activity of tamarind leaf capsule (Tamarindus indica L.) and determine the effective dose that acts as an anti-diabetic. This study used male white rabbits that had previously been induced with streptozotocin at a dose of 60 mg/kgBW. Rabbits were divided into five treatment groups, namely CMC-Na (negative control), glibenclamide 0.45 mg/kgBW (positive control) and tamarind leaf capsules at a dose of 50 mg/kgBW, 100 mg/kgBW and 200 mg/kgBW. The results obtained were analyzed by statistical test One way ANOVA and Tukey test. The results obtained that tamarind leaf capsules at a dose of 200 mg/kgBW have antidiabetic activity close to glibenclamide at a dose of 0.45 mg/kgBW. The results of the One Way ANOVA test obtained a significance value (p < 0.05) and when continued with the Tukey test, the results showed that tamarind leaf capsules at a dose of 100 mg/kgBW and a dose of 200 mg/kgBW had no significant difference in decreasing blood glucose levels. This means that both doses are effective as antidiabetic doses which are comparable to glibenclamide 0.45 mg/kgBW.